INCOME TARGETS AND POVERTY OF RUBBER SMALLHOLDERS IN FOUR STATES OF MALAYSIA - Jamil Wee, Siti Murni Wee; Singaravelloo, Kuppusamy (PLANNING MALAYSIA, 2018)
Both rubber and oil have contributed significantly to Malaysia’s revenues and job creations especially for those in the rural areas. Malaysia now stands at third after Thailand and Indonesia in natural rubber production. However, the country’s natural rubber productivity began to decline since late 2011 and would probably deteriorate through 2016 as consumption growth weakens in China - the largest importer, curbing prices of the raw material used in everything from tyre to medical gloves and condoms. The declining rubber price has moved the smallholders who mostly live in rural areas into serious poverty. This has led the smallholders, who sustain latex production, to suffer and find alternative jobs to sustain. This has dampened the government’s intention to ensure smallholders earn at least RM2,500 per month by 2015 and further to RM4,000 by 2020. The key objectives of this paper are to determine the poverty level, whether this policy has been met, and the impact of the reducing price of the commodity on the smallholders’ spending patterns. The study finds a large proportion of this group fall into the hardcore poverty category, which deviates very much from the national poverty levels pronounced by the government. More needs to be done to assist this impoverished group.